Transmitter for Professional Microphone - Árva, G. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
This project deals with the design of a transmitter in a wireless microphone system, which connects to microphone through the XLR connector. The paper contains description of individual blocks which are necessary for processing and transmitting the signal generated by the microphone, describes methods of frequency modulation using a phase locked loop and compares their advantages and disadvantages. As the last, it deals with the choosing of an antenna and its adjustment to appropriate dimensions.
Keywords: microphone; wireless microphone; transmitter; phase-locked loop; frequency synthesizer; frequency modulation; meander antenna